COMBINED METHODS OF ENGINEERING OF CONTACT SURFACES OF TRIBOLOGY SYSTEMS - Kharchenko, Volodymyr; Humenyuk, Ihor; Кornienko, Anatoliy; Ivanytskyi, Maksym (Problems of Friction and Wear, 2024)
The issues of ensuring the durability and reliability of equipment, increasing wear resistance and expanding the range of operation of friction pairs in extreme operating conditions require solutions related to innovative technologies for the formation of wear-resistant surfaces that can significantly increase the efficiency of using hardening methods, creating new ones and improving existing ones. A brief review of the combined methods of engineering contact surfaces of tribological systems is carried out. The perspective of using this direction to expand the range of use of discrete protective structures, namely in the conditions of fretting, fretting fatigue, and limit friction, is shown.